2003
DOI: 10.1002/sia.1628
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption behaviour of C2H5SCH3 on Ag(111) and Ag(UFP) surfaces

Abstract: The adsorption behaviour of ethylmethylsulfide .C 2 H 5 SCH 3 / on Ag(111) and ultrafine particle Ag, Ag(UFP), surfaces has been studied by near-edge x-ray absorption fine structure and x-ray photoelectron spectroscopy techniques. It is found that C 2 H 5 SCH 3 adsorbs molecularly on the Ag(111) surface but dissociates on Ag(UFP). On the Ag(111) surface the molecule shows polarization dependence. The S-C 2 H 5 and S-CH 3 bonds are found to be tilted at angles of 31 ± 5• and 21 ± 5• from the surface, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Since most adsorption studies are carried out under ultrahigh vacuum (UHV) conditions, usually metals are used as substrates. It is by now well established that molecules having thiol (−SH) as endgroups can show strong bonds to surfaces because of the special affinity between sulfur and certain metals, e.g., Au surfaces, Cu surfaces, and Ag surfaces . Furthermore, theoretical studies have shown a strong affinity between transition metals and sulfur .…”
Section: Introductionmentioning
confidence: 99%
“…Since most adsorption studies are carried out under ultrahigh vacuum (UHV) conditions, usually metals are used as substrates. It is by now well established that molecules having thiol (−SH) as endgroups can show strong bonds to surfaces because of the special affinity between sulfur and certain metals, e.g., Au surfaces, Cu surfaces, and Ag surfaces . Furthermore, theoretical studies have shown a strong affinity between transition metals and sulfur .…”
Section: Introductionmentioning
confidence: 99%